Psychological Treatments and Psychotherapies in the Neurorehabilitation of Pain: Evidences and Recommendations from the Italian Consensus Conference on Pain in Neurorehabilitation - Castelnuovo, Gianluca; Giusti, Emanuele M.; Manzoni, Gian Mauro; Saviola, Donatella; Gatti, Arianna; Gabrielli, Samantha; Lacerenza, Marco; Pietrabissa, Giada; Cattivelli, Roberto; Spatola, Chiara A. M.; Corti, Stefania; Novelli, Margherita; et al. (Frontiers in Psychology, 2016)
Background It is increasingly recognized that treating pain is crucial for an effective care of the person in the setting of the neurological rehabilitation. The Italian Consensus Conference on Pain in Neurorehabilitation was constituted with the purpose to identify the best practices that can be used in this context. Along with drug therapies and physical interventions, psychological treatments have been proven to be some of the most valuable tools that can be used within a multidisciplinary approach for fostering a reduction in pain intensity. However, there is the need to elucidate what forms of psychotherapy could be matched with the specific pathologies that are taken in charge by the neurorehabilitation teams. Objectives To extensively assess the available evidence which supports the use of psychological therapies for pain reduction in neurological diseases. Methods A systematic review of the studies evaluating the effect of psychotherapies on pain intensity in neurological disorders was performed through an electronic search using PUBMED, EMBASE and the Cochrane Database of Systematic Reviews. Based on the level of evidence of the included studies, recommendations were outlined separately for the different conditions. Results The literature search yielded 2352 results and the final database included 400 articles. The overall strength of the recommendations was medium/low. The different forms of psychological interventions, including Cognitive – Behavioral Therapy, cognitive or behavioral techniques, Mindfulness, hypnosis, Acceptance and Commitment Therapy, Brief Interpersonal Therapy, virtual reality interventions, the different forms of biofeedback and mirror therapy were found to be effective for pain reduction in pathologies such as musculoskeletal pain, fibromyalgia, Complex Regional Pain Syndrome, Central Post – Stroke pain, Phantom Limb Pain, pain secondary to Spinal Cord Injury, multiple sclerosis and other debilitating syndromes, diabetic neuropathy, Medically Unexplained Symptoms, migraine and headache. Conclusions Psychological interventions and psychotherapies are safe and effective treatments that can be used within an integrated approach in patients undergoing neurological rehabilitation for pain. The different interventions can be specifically selected depending on the disease being treated. A table of evidences and recommendations from the Italian Consensus Conference on Pain in Neurorehabilitation is also provided in the final part of the paper.